Development of Mathematical Literacy Problems Based on the Ethnomathematics of Acehnese Culture - Maulina, Suci; Isa, Muhammad; Helmi, Rahil; Riski, Novia; Safitri, Eka (Jurnal Pendidikan MIPA, 2025)
This study aims to develop mathematical literacy problems based on the ethnomathematics of Acehnese culture. This study is motivated by the lack of resources relevant to local culture, which has hindered Acehnese mathematics teachers from implementing ethnomathematics in their classrooms. Ethnomathematics is regarded as an effective approach to enhance students’ mathematical literacy. Moreover, the integration of culture into mathematics learning has also become part of a government program in response to the low mathematical literacy performance of Indonesian students in the Program for International Student Assessment (PISA). This developmental research employed the Thiagarajan Four-D model, comprising Define, Design, Development, and Disseminate. However, this study focused only on the first three phases. The define phase entails a systematic needs analysis encompassing curriculum, student characteristics, and conceptual aspects. The design phase produces a preliminary prototype of mathematical literacy problems contextualized in Acehnese culture. The develop phase involves expert validation and iterative evaluation through one-to-one evaluations, small-group trials, and classroom field testing, with revisions incorporated to enhance validity, reliability, and pedagogical relevance. This study involved 41 students from a senior high school in Aceh and five validators. Data were gathered from validation and practicality questionnaires, interviews, and tests. Data were then analyzed descriptively. The result revealed that 19 out of 20 problems were valid. The problems were also considered practical and potentially effective for implementation in mathematics classrooms. The development of these problems provides a useful resource for mathematics teachers in Aceh. The study result suggests that ethnomathematics problems are beneficial in improving students’ mathematical literacy. The value of culture embedded in the mathematical problems raises students’ awareness and understanding of their local culture. These findings suggest that integrating local culture into mathematics instruction can help teachers design meaningful learning experiences that enhance both mathematical understanding and cultural awareness.   Keywords: acehnese culture, developmental research, ethnomathematics, mathematical literacy problem, mathematics learning.